Conspiratorial Narratives in Violent Political Actors' Language. (October 2019) - Baele, Stephane J.
This article articulates the concept of "conspiratorial narratives"—defined as stories which integrate a large range of events and archetypal characters from past and present in a single teleological explanation for the alleged suffering of a given social group—and argues that this particular linguistic construct is a key marker of extremist language. Using three different cases to illustrate our theoretical contribution (Nazi propaganda, Rwandan genocidaires' radio, IS' messaging), we show that paying attention to conspiratorial narratives leads us to significantly revise classic accounts of violent actors' language, and provides a better understanding of the link between that language and violence itself—more precisely, why violence happens, how much violence is directed to whom, and when it occurs.